EFEKTIVITAS PENGGUNAAN MEDIA INTERAKTIF PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH TSANAWIYAH BADRUSSALAM INDONESIA DESA KADEMANGAN KECAMATAN PAGELARAN - Ana Alfiana Dwi Maisaroh; Zainuddin Fanani (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
The purpose of this study is to explain interactive media, the factors that support and hinder its implementation, and to evaluate the effectiveness of using interactive media in learning. This study employs a case study design using qualitative methods. Data collection techniques included in-depth interviews, direct observation, and documentation. Data analysis in this study used the Miles and Huberman approach. Triangulation techniques were applied to ensure data validity. The data sources for this study were the madrasah principal, religious teachers specifically those teaching SKI and the students. This study applied data presentation, reduction, and verification analysis. The research findings are as follows: First, the use of interactive learning media based on projectors and laptops, such as instructional videos, illustrated texts, and instructional videos or films, utilizes interactive projector media. Second, the presence of supporting factors in the form of adequate infrastructure (network) so that teachers can easily access materials and textbooks. Third, the presence of inhibiting factors for learning media created using projectors such as educational videos, material brochures, and illustrated texts includes students who have not yet fully grasped the content and students who are less responsive and less enthusiastic during the learning process due to the historical nature of the material. Fourth, to determine the effectiveness of using interactive media for teaching the history of Islamic culture at Madrasah Tsanawiyah Badrussalam in Indonesia. It has been proven that the use of this interactive media improves understanding of the material through the presentation of information via images and sound, leads to better information retention, helps students understand complex concepts, provides clear visual representations and practical contexts, and increases student engagement through an attractive and interactive format. Finally, it facilitates the evaluation process of the taught material.